Tomoi - Natashah Md. Nor; Rusli Harun; Amelia Abd. Aziz (Malaysia : UAS Communications (M), 1997)
The story of tomoi which is the ancient forms of martial arts in northern parts of Kedah
Executive producer, Najib Shafion, Zabidi Sanip ; script, Amelia Abd. Aziz
Narrator: Reemy Abdul Rahman
Keywords: Hand-to-hand fighting; Martial arts; Self-defense